Analysis of the Influence of Work-Life Balance and Work Environment on Turnover Intention: The Mediating Role of Remuneration (Case Study at Private Company X in Central Jakarta) - Kurnia Syafitri (Green Publisher Indonesia, 2026)
Work-life balance (WLB) and employee engagement are important factors that can drive a company's sustainable growth. Turnover intention has become a common problem faced by many companies, resulting in an increase in employee turnover rates. This has a significant impact on the sustainability of the company's operations. This study aims to test the influence of work-life balance (WLB) and work environment on turnover intention, with remuneration as an intervening variable, among employees of Company X in Central Jakarta. Using a quantitative method with the Partial Least Squares (PLS) analysis technique, data were collected from 120 respondents through a questionnaire. The results of the study show that the work environment has a negative and significant effect on turnover intention. In contrast, WLB was found to have a positive and significant effect on turnover intention in this sample. Remuneration has been proven to significantly mediate the influence of the work environment on employee exit intention but is unable to mediate the relationship between WLB and exit intention.